2013
DOI: 10.1097/pai.0b013e31827d7f16
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class I and II Expression in Idiopathic Inflammatory Myopathy

Abstract: Immunostaining for MHC I and II is a useful adjunctive test in diagnosis and subclassification of IIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
5
28
2
1
Order By: Relevance
“…In this study, we found a high specificity (0.891) and moderate sensitivity (0.605) for MHC-II expression in IIM and, as shown in Figure 5 found positive expression with varying sensitivities (25%-93%) or specificity (100%) in IIM [7,36]. MHC-II expression is necessary to activate T-helper cells and to initiate an immune response, and muscle cells can act as facultative antigen-presenting cells through the expression of MHC-II molecules [19,37].…”
Section: Text 14supporting
confidence: 62%
See 1 more Smart Citation
“…In this study, we found a high specificity (0.891) and moderate sensitivity (0.605) for MHC-II expression in IIM and, as shown in Figure 5 found positive expression with varying sensitivities (25%-93%) or specificity (100%) in IIM [7,36]. MHC-II expression is necessary to activate T-helper cells and to initiate an immune response, and muscle cells can act as facultative antigen-presenting cells through the expression of MHC-II molecules [19,37].…”
Section: Text 14supporting
confidence: 62%
“…A number of previous studies, which have been summarised in Tables 1 and 2, have reported positive immunohistochemical staining for MHC in IIM and other muscle conditions. Some studies have also addressed the diagnostic value of MHC expression with different methodologies and results [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…MHC-II staining appears to be more specific, and is especially prominent in IBM [29] compared to the other IM. A recent report describes MHC-II staining to reach 100% in IBM tissues, while only 40% of NAM tissues were positive [30].…”
Section: Major Histocompatibility Complexesmentioning
confidence: 91%
“…The MHC class 1 expression on the sarcolemma, which is absent in normal muscle fibers, is upregulated in patients with IMs (29)(30)(31). Additionally, MHC class 2 is not expressed on normal myofibers, and some investigators have detected this antigen in specimens from patients with IMs (32)(33)(34)(35). HLA-DR was overexpressed on the sarcolemma in the PM group, but weakly expressed in the DM and CAM groups in the present study.…”
Section: Discussionmentioning
confidence: 99%